Superconductivity in solid benzene molecular crystal. (23rd May 2018) - Zhong, Guo-Hua; Yang, Chun-Lei; Chen, Xiao-Jia; Lin, Hai-Qing
Abstract: Light-element compounds hold great promise of high critical temperature superconductivity judging from the theoretical perspective. A hydrogen-rich material, benzene, is such a kind of candidate but also an organic compound. A series of first-principles calculations are performed on the electronic structures, dynamics properties, and electron–phonon interactions of solid benzene at high pressures. Benzene is found to be dynamically stable in the pressure range of 180–200 GPa and to exhibit superconductivity with a maximum transition temperature of 20 K at 195 GPa. The phonon modes of carbon atoms are identified to mainly contribute to the electron–phonon interactions driving this superconductivity. The predicted superconductivity in this simplest pristine hydrocarbon shows a common feature in aromatic hydrocarbons and also makes it a bridge to organic and hydrogen-rich superconductors.